The influence of social network size on speech perception. Issue 10 (October 2018) - Lev-Ari, Shiri
Infants and adults learn new phonological varieties better when exposed to multiple rather than a single speaker. This article tests whether having a larger social network similarly facilitates phonological performance. Experiment 1 shows that people with larger social networks are better at vowel perception in noise, indicating that the benefit of laboratory exposure to multiple speakers extends to real life experience and to adults tested in their native language. Furthermore, the experiment shows that this association is not due to differences in amount of input or to cognitive differences between people with different social network sizes. Follow-up computational simulations reveal that the benefit of larger social networks is mostly due to increased input variability. Additionally, the simulations show that the boost that larger social networks provide is independent of the amount of input received but is larger if the population is more heterogeneous. Finally, a comparison of "adult" and "child" simulations reconciles previous conflicting findings by suggesting that input variability along the relevant dimension might be less useful at the earliest stages of learning. Together, this article shows when and how the size of our social network influences our speech perception. It thus shows how aspects of our lifestyle can influence our linguistic performance.